Pengaruh Pengalaman dan Independensi terhadap Kualitas Audit dengan Etika Auditor sebagai Variabel Moderating Pada Kantor Akuntan Publik Kota Medan - Maisyarah Salsabila; Widia Astuty; Irfan Irfan (Jurnal Riset AKuntansi dan Bisnis, 2021)
This study aims to examine and analyze whether there is an effect of experience, independence, time pressure, and audit fees on audit quality as moderated by auditor ethics. This type of research is descriptive quantitative with an associative approach. This research was conducted using documentation and survey methods by distributing questionnaires to external auditors who work at the Public Accounting Firm in Medan. The sampling technique used stratified random sampling with the Slovin formula as many as 69 respondents. Data were analyzed using structural equation model partial least square (SEM-PLS). The results of this study indicate that experience has an effect on audit quality. However, independence has no effect on audit quality. In addition, this study also found that auditor ethics was able to moderate the effect of experience and independence on audit quality. For this reason, it is hoped that auditors will continue to improve the quality of good audits, public accountants must have sufficient experience and knowledge in their fields by conducting evaluations or sufficient training through formal or informal education and auditors must improve their ability to collect any information needed in the field. making audit decisions where it must be supported by an independent attitude.